DOMAIN NAMES AS ATYPICAL OBJECTS OF CIVIL LAW: PROBLEMS OF UNDERSTANDING - Tsybizova, Stella (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of this article is to consider problematic issues regarding the understanding of domain names as atypical objects of civil law. For this purpose, the conceptual approaches of civil scientists regarding domain names and their place in the civil law system were analyzed. The concept of assigning domain names to objects of intellectual property law, in particular, to means of individualization, as well as to such objects of civil law as property and property rights, is subject. The methodological basis of the research is general scientific and special methods of cognition. to reasoned criticism. The use of these methods made it possible to describe problematic issues regarding the understanding of domain names as atypical objects of civil law. Results: the actual legal relations arising in connection with domain names and their participation in civil circulation provide reasons at the level of legal doctrine to define a domain name as an atypical object of civil law, and the economic value of a domain name allows defining the latter as a good. Discussion: the specificity of domain names and the impossibility of attributing the latter to traditional (typical) objects of civil rights such as property, property rights, or objects of intellectual property rights determine the need for further theoretical development of domain names as objects of civil rights, namely as non-typical objects. The norms of the current legislation of Ukraine characterize domain names as means of addressing and identifying computers and resources on the Internet. At the same time, at the legislative level, the legal regime of domain names is not established. A separate law or collection of legislation on the legal regulation of domain names has not yet been developed in Ukraine. At the same time, the actual legal relations arising in connection with domain names and their participation in civil turnover give reasons at the level of legal doctrine to define a domain name as a separate object of civil rights, and the economic value of a domain name allows defining the latter as a good. Difficulties also arise regarding the assignment of domain names to classic (typical) objects of civil rights. The theory regarding the classification of domain names as objects of intellectual property law is untenable, because domain names are not the result of intellectual, creative activity and are not identical in their main purpose to means of individualization. Therefore, attributing domain names to property or property rights does not comply with the norms of national legislation. Thus, the specificity of domain names and the impossibility of attributing the latter to traditional (typical, classical) objects of civil rights, such as property, property rights, or objects of intellectual property rights, necessitate the further theoretical development of domain names as objects civil rights, namely, as atypical objects of civil rights.